2022
DOI: 10.1155/2022/4802814
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Influence of Commute Time Tolerance Threshold on Commute Mode Choice Based on the Semicompensatory Model

Abstract: The tolerance threshold of commute time (TTCT) reflects the longest commute time that commuters can tolerate from home to the workplace. When the commute time exceeds the TTCT, the commuting utility significantly reduces, which has a nonlinear influence on commuting mode choice. To reveal the nonlinear relationship between the commuting utility and commute time, the TTCT is introduced to constrained multinomial logit (CMNL) model based on the semicompensatory decision-making mechanism. In addition, an empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Additionally, the authors observed that service value, switching costs, and trust have direct and positive effects on loyalty, whereas the attractiveness of competitors has a negative one. In another study, Yan et al [35] used SEM to explore the relationship between socioeconomic and travel characteristics and the degree of influence on the willingness to travel by bus, finding that an individual's economic status plays a crucial role in choosing a preferred mode of transportation. For example, individuals are more likely to drive if they can park their cars easily, quickly, and affordably.…”
Section: Using Sem To Assess Passenger Satisfaction With Intercity Busesmentioning
confidence: 99%
“…Additionally, the authors observed that service value, switching costs, and trust have direct and positive effects on loyalty, whereas the attractiveness of competitors has a negative one. In another study, Yan et al [35] used SEM to explore the relationship between socioeconomic and travel characteristics and the degree of influence on the willingness to travel by bus, finding that an individual's economic status plays a crucial role in choosing a preferred mode of transportation. For example, individuals are more likely to drive if they can park their cars easily, quickly, and affordably.…”
Section: Using Sem To Assess Passenger Satisfaction With Intercity Busesmentioning
confidence: 99%